Impact of partial interpenetration in a hybrid ultramicroporous material on C2H2/C2H4 separation performance. Issue 28 (21st March 2018) - O'Nolan, Daniel; Madden, David G.; Kumar, Amrit; Chen, Kai-Jie; Pham, Tony; Forrest, Katherine A.; Patyk-Kazmierczak, Ewa; Yang, Qing-Yuan; Murray, Claire A.; Tang, Chiu C.; Space, Brian; Zaworotko, Michael J.
Abstract : Phases of a 2-foldpcu hybrid ultramicroporous material (HUM), SIFSIX-14-Cu-i, exhibiting 99%, 93%, 89%, and 70% partial interpenetration have been obtained. Abstract : Phases of a 2-foldpcu hybrid ultramicroporous material (HUM), SIFSIX-14-Cu-i, exhibiting 99%, 93%, 89%, and 70% partial interpenetration have been obtained. 1 : 99 C2 H2 /C2 H4 gas separation studies reveal that as the proportion of interpenetrated component decreases, so does the separation performance.